Why was there no religious war in premodern East Asia?. (December 2014) - Kang, David C.
In premodern East Asia, Korea, Japan, Vietnam, and China rarely experienced anything like the type of religious violence that existed for centuries in historical Europe, despite having vibrant religious traditions such as Confucianism, Buddhism, Daoism, and numerous folk religions. How do we explain a region in which religion was generally not a part of the explanation for war and rebellion? A unique data set of over 950 entries of Chinese and Korean violence over a 473-year span allows granular measurement of religious violence. I argue that the inclusivist religions of historical East Asia did not easily lend themselves to appropriation by political leaders as a means of differentiating groups or justifying violence. Addressing the paucity of religious war in historical East Asia is theoretically important because it challenges a large body of scholarly literature that finds a universal causal relationship between religion and war that is empirically derived mainly from the experience of only Christianity and Islam. In contrast, it may be that certain types of religious traditions are less amenable to mass mobilization for violence. Moving beyond Christianity and Islam to include East Asian religious traditions promises both to address a potentially serious issue of selection bias and also to be a rich field for theorizing about the relationship between religion and war.